MODIFIED ATMOSPHERE PACKAGING IN THE TROPICAL FRUIT EXPORT CHAIN: EFFICIENCY, LIMITATIONS, AND LOGISTICAL IMPLICATIONS (Editora Impacto Científico, 2025)
Modified Atmosphere Packaging (MAP) has been consolidated as a strategic technology in the postharvest conservation of tropical fruits, contributing to the reduction of losses, the maintenance of quality, and the feasibility of exports to distant markets. This article presents a critical review of the advances, limitations, and logistical implications of MAP, with emphasis on mangoes, based on the analysis of national and international scientific literature published between 2010 and 2025, complemented by consolidated studies from previous decades. The review highlights the physiological principles of MAP, the distinctions between passive and active approaches, the importance of proper packaging material selection, and its interaction with refrigeration. Practical cases with mango cultivars such as ‘Keitt,’ Ataulfo,’ Tommy Atkins,’ and ‘Palmer’ demonstrate that the response to the technique depends on the cultivar, film permeability, and logistical conditions. Although complementary technologies such as ethylene filters may add value in certain contexts, the data indicate that their application should be carefully evaluated. The results suggest that the effectiveness of MAP is related to technical planning, understanding product physiology, and the adaptation of solutions to the operational realities of the export chain. It is concluded that, when properly applied, MAP can represent a competitive advantage for tropical fruit production, expanding access to international markets with lower environmental impact and greater added value.DOI: https://doi.org/10.56238/edimpacto2025.090-039